Impact of soil texture on different organic carbon pools in Sirsa district of western Haryana, India - Verma, Vijendra Kumar; Jakhar, Devender Singh; Raj, Dev; Choudhary, Sunita; Fagodiya, Ram Kishor; Ranjan, Supriya; Yadav, Saloni; Dhayal, Priya; Bhinchar, Sudhir (Journal of Soil Salinity and Water Quality, 2023)
Soil organic carbon (SOC) pools are important in maintaining soil productivity and influencing the CO2 loading into the atmosphere. Different soil textural classes of Sirsa district, Haryana were compared for SOC and its fractions viz; active (very labile, VLSOC; labile, LSOC) and passive (less labile, LLSOC; non-labile, NLSOC) pools. Maximum OC (0.66%) and TOC (0.78%) was observed in clay loam texture compared to loamy sand, sandy loam, loam and clay loam texture. Similarly, highest VLSOC (0.47%) and LSOC (0.11%) pools were recorded in sandy soils whereas highest LLSOC (0.12%) and NLSOC (0.18%) pools were recorded in clay loam soils compared to other textures. Highest RI1 (0.50) and RI2 (0.23) were found in clay loam soils whereas highest carbon lability index (CLI) was found in sandy (3.96) soils. The texture of soil significantly impacted SOC and its associated pools. VLSOC had significant positive correlation with LSOC (p≤0.05), while LSOC showed significant positive correlation with VLSOC (p≤0.01). Similarly, LLSOC had significant positive correlation with NLSOC reciprocated by NLSOC exhibiting a significant positive correlation with LLSOC (p≤0.01). Therefore, correlation amongst the pools of C showed that most of the pools were significantly correlated with each other.